Partial replacement of soybean with local alternative sources: effects on behavior, cecal microbiota, and intestinal histomorphometry of local chickens - Özkan, Sezen; Bay, Veysel; Cömert Acar, Muazzez; Yalcın, Servet (Frontiers in Veterinary Science, 2024)
Interest in partially replacing soybean meal in poultry diets with alternative protein sources such as agri-industrial by-products and black soldier fly (BSF, Hermetia illucens) has gained significant attention due to sustainability concerns. This study aimed to evaluate the effects of broiler diets in which soybean meal was partially substituted with agri-industrial by-products with or without BSF larvae meal, on the behavior, intestinal histomorphometry, and microbiome profile of a local broiler chicken strain. There were three dietary treatments. (1) A corn-soybean-based diet (Control), (2) a diet in which soybean was partly replaced (SPR) with local agri-industrial by-products, namely sunflower meal, brewers' dried grain, and wheat middlings, and (3) a diet in which BSF (5%) meal was added to SPR (SPR+BSF). Behavior was recorded on days 14, 35, and 49 at the pen level. On day 55, intestinal segments and cecal contents were collected from eight chickens per pen for histomorphometry and microbiome analysis. Dietary manipulations did not affect the behavior of broiler chickens (P > 0.05) suggesting that the experimental diets had no influence on behavior. A significant interaction between the intestinal segment and diets revealed that the SPR and SPR+BSF diets decreased duodenal villus height (VH) compared to the control diet (P < 0.05). However, this effect was not consistent across all of intestinal segments. Diet did not affect villus height to crypt depth ratio (VH/CD; P > 0.05), indicating no significant impact on the absorptive capacity of the digestive system. Firmicutes and Bacteroidetes were the dominant phyla in the cecal samples. Colidextribacter and Oscillibacter spp. were more abundant in chickens fed the SPR diet compared to those fed the control diet. The SPR+BSF diet resulted in higher abundance of Rikenella and Colidextribacter spp. compared to the control diet, while Desulfovibrio, Ruminococcus torques group, and Lachnoclostridium were more abundant in the ceca of birds fed the SPR diet than those fed SPR+BSF. In conclusion, replacement of soybean with agri-industrial by-products and BSF larvae meal could regulate the cecal microbiota composition without negatively affecting the behavior and intestinal histomorphometry of the local chickens.